Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/jxb/eri163
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides and phosphatidic acid regulate pollen tube growth and reorientation through modulation of [Ca2+]c and membrane secretion

Abstract: The maintenance of a calcium gradient and vesicle secretion in the apex of pollen tubes is essential for growth. It is shown here that phosphatidylinositol-4,5-bisphosphate (PIP2) and D-myo-inositol-1,4,5-trisphosphate (IP3), together with phosphatidic acid (PA), play a vital role in the regulation of these processes. Changes in the intracellular concentration of both PIP2 and IP3 (induced by photolysis of caged-probes), modified growth and caused reorientation of the growth axis. However, measurements of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
123
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 34 publications
8
123
0
2
Order By: Relevance
“…Most PLD genes are induced by hormones (IAA, GA, ABA) or stress stimuli (salt and drought), indicating the possible involvement of PLDs in hormone effects and stress responses. In Arabidopsis, PLDs have been shown to be involved in multiple processes; for example, PLDα1 is involved in the signal transduction of ABA, GA, and ethylene, and in senescence, water loss and freezing tolerance; PLDδ1 is a positive regulator of stress response, and also acts as a bridge between the plasma membrane and microtubule [13,16]; PLDζ2 is involved in phosphorusdeficiency-induced root elongation and digalactosyldiacylglycerol accumulation [41,42], and is required for auxin response [26]. In rice, the distinct expression patterns of different PLD members in the presence of plant hormones and in stress responses reveal the multiple and specific roles Phospholipase D family in rice 892 npg of PLDs.…”
Section: Pld Family In Oryza Sativamentioning
confidence: 99%
See 1 more Smart Citation
“…Most PLD genes are induced by hormones (IAA, GA, ABA) or stress stimuli (salt and drought), indicating the possible involvement of PLDs in hormone effects and stress responses. In Arabidopsis, PLDs have been shown to be involved in multiple processes; for example, PLDα1 is involved in the signal transduction of ABA, GA, and ethylene, and in senescence, water loss and freezing tolerance; PLDδ1 is a positive regulator of stress response, and also acts as a bridge between the plasma membrane and microtubule [13,16]; PLDζ2 is involved in phosphorusdeficiency-induced root elongation and digalactosyldiacylglycerol accumulation [41,42], and is required for auxin response [26]. In rice, the distinct expression patterns of different PLD members in the presence of plant hormones and in stress responses reveal the multiple and specific roles Phospholipase D family in rice 892 npg of PLDs.…”
Section: Pld Family In Oryza Sativamentioning
confidence: 99%
“…Treatment with the PLD-specific inhibitor 1-butanol results in inhibited seed germination, altered emergence of the radicle and cotyledons, and abnormal root elongation and pattern formation of root hairs [14,15]. It was also shown that PLD and PA are critical for pollen germination and pollen tube elongation; reduced production of PA by PLD resulted in inhibited pollen tube germination and tip growth, and altered apical polarity of the pollen tube [16]. In addition, the actin and microtubule structures were severely altered under 1-butanol treatment [14,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular level of PA is increased under various stress conditions, such as treatments of abscisic acid (ABA) (4), osmotic stress (5-7), oxidative stress (8), pathogen infection (9,10), and cold and freezing conditions (11)(12)(13). In addition, PA is involved in regulating normal plant growth and development, particularly in roots (14,15) and pollen tubes (16,17).…”
mentioning
confidence: 99%
“…PIP 2 binds different actin binding proteins, including villin/gelsolin, and profilin (Yin and Janmey, 2003). IP 3 stimulates the release of Ca 21 from internal stores, and consequently may modulate the apical gradient of the ion (Franklin-Tong et al, 1996;Malhó , 1998;Monteiro et al, 2005). It seems pertinent to consider these growth-associated factors with the Rops, with which they may closely interact (Kost et al, 1999).…”
mentioning
confidence: 99%